Differences in per capita rates of revascularization and in choice of revascularization procedure for eleven states - Wu Chuntao; Hannan Edward L; Chassin Mark R (BMC, 2006)
Abstract Background A few studies have investigated differences in elective procedure rates across small and medium sized referral regions. The purposes of this study are to investigate differences in revascularizations across 11 entire states and to investigate differences in choice of revascularization procedure (percutaneous coronary intervention (PCI) vs. coronary artery bypass graft (CABG) surgery). Methods Age-sex adjusted rates per 100,000 population who were 20 or older were calculated for PCI, CABG surgery, and total revascularization for each state. Also, the risk-adjusted proportion of revascularized patients who underwent PCI was calculated for each state and differences were compared. Results We found variations in procedures performed per capita of 1.83-fold for PCI, 1.54-fold for CABG surgery, and 1.54-fold for total revascularization. For patients undergoing revascularization of two or more vessels, the age/sex adjusted maximum rate of 224 per 100,000 population over 20 years old in Florida was 53% higher than the minimum rate of 146 in Colorado. Higher catheterization rates per 1,000 Medicare enrollees and higher percent of white patients were significant predictors of higher revascularization rates, and density of specialists was a significant predictor of catheterization rate. The risk-adjusted percentage of revascularized patients with two or more arteries attempted who underwent PCI ranged from 10.4% in Oregon to 29.0% in Iowa. Conclusion There are reasonably large differences among states in total revascularization rates and in type of revascularization among revascularization. These differences appear to be related to practice pattern differences. Future effort should be devoted to understanding the reason for these differences and the impact on patients' health and survival.